Trade Union Development and Industrial Relations in the British West Indies - Dion, Gérard (Relations industrielles / Industrial Relations, 1961)
The article reviews the book, "Trade Union Development and Industrial Relations in the British West Indies," by William S. Knowles. A publication of the Institute of Industrial Relations, University of California.